MEDIATING ROLE OF CUSTOMER EXPERIENCE BETWEEN INNOVATION AND PERFORMANCE: A STUDY OF QUICK SERVICE RESTAURANTS (QSRs) - Singh, Rajesh; Sarangal, Rajani Kumari; Sharma, Priyanka (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2020)
The primary rationale of this study is to examine the impact of innovation on customer experience (CP) and customer performance (CP) in the Quick Service Restaurants (QSRs). The study further analyzes the impact of customer experience (CE) on customer performance (CP). Moreover, the study also tends to approach the mediating role of customer experience in between innovation and customer performance. A total of 322 questionnaires were analyzed using exploratory factor analyses (EFA) and confirmatory factor analysis (CFA) to identify and confirm the various factors in the study respectively. Structural equation modeling has been used to test the relationship between the constructs. The study finds that innovation positively impacts CE and CP. Further, the study also verified that CE positively impacts CP and it acts as a partial mediator between CE and CP. Research is restricted to the QSRs of Jammu region which includes McDonald’s, KFC, Domino’s Pizza, and Pizza Hut. This study recommends the implementation of innovative practices in QSRs to enhance the CE that in turn will leads to higher CP in selected QSRs.